Analisis Kebijakan Pendidikan Dalam Meningkatkan Budaya Mutu Di SD IT Tafizil Qur'an Yayasan Islamic Center Sumatera Utara (YIC-SU) - Ahmad Raihan Azizi; Leni Hermita Hasibuan; Lusi Mqfiroh (Lembaga Pengembangan Kinerja Dosen, 2024)
Education policy analysis in improving quality culture through a process of predetermined stages to formulate problems that nanitnya bring up alternative policies as problem solving and improve the quality of education. The purpose of this study was to analyse the application of educational policy analysis in improving quality culture at SD - IT Tafizil Qur'an Yayasan Islamic Center North Sumatra (YIC-SU). This research method uses qualitative research using primary and secondary data collection techniques. Data sources include interviews, observation and documentation. The results of this study indicate that SD - IT Tafizil Qur'an (YIC-SU) in conducting educational policy analysis to improve quality culture by conducting several stages, namely 1). Problem formulation, 2). Policy agenda and formulation of policy alternatives, 3). Policy determination. The results obtained by SD - IT Tafizil Qur'an (YIC-SU) can build a good and sustainable quality culture so that it continues to be a school that is in great demand.